1998
DOI: 10.1128/aem.64.9.3238-3245.1998
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid (DNA, RNA) Quantification and RNA/DNA Ratio Determination in Marine Sediments: Comparison of Spectrophotometric, Fluorometric, and HighPerformance Liquid Chromatography Methods and Estimation of Detrital DNA

Abstract: In this study, we compared three methods for extraction and quantification of RNA and DNA from marine sediments: (i) a spectrophotometric method using the diphenylamine assay; (ii) a fluorometric method utilizing selective fluorochromes (thiazole orange for total nucleic acids and Hoechst 33258 for DNA); and (iii) a high-pressure liquid chromatography (HPLC) method which uses a specific column to separate RNA and DNA and UV absorption of the nucleic acids for quantification. Sediment samples were collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 42 publications
0
52
1
Order By: Relevance
“…However, previous studies have shown that an increased proportion of SSU rRNA molecules to SSU rRNA genes per cell can be observed in highly metabolically active cells (Nomura et al, 1984). Therefore, highly active taxa with low cell counts may be underrepresented or not detected in DNA-derived clone libraries because SSU rRNA gene targets are at or below detection limits (Dell'Anno et al, 1998;Nogales et al, 2001;Mills et al, 2005). The opposite would be observed if the cells were numerous but had low or no metabolic activity.…”
Section: Change In Subsurface Activity and Microbial Diversity Acrossmentioning
confidence: 97%
“…However, previous studies have shown that an increased proportion of SSU rRNA molecules to SSU rRNA genes per cell can be observed in highly metabolically active cells (Nomura et al, 1984). Therefore, highly active taxa with low cell counts may be underrepresented or not detected in DNA-derived clone libraries because SSU rRNA gene targets are at or below detection limits (Dell'Anno et al, 1998;Nogales et al, 2001;Mills et al, 2005). The opposite would be observed if the cells were numerous but had low or no metabolic activity.…”
Section: Change In Subsurface Activity and Microbial Diversity Acrossmentioning
confidence: 97%
“…Prior to nucleic acid extraction, one set of sediment samples were exposed to EMA. Since extracellular DNA may adsorb to sediment particles and survive for many years as intact DNA (Dell'Anno et al, 1998;Demanèche et al, 2001), an EMA pre-treatment of sediment samples was performed. Like ethidium bromide, EMA is a DNA/RNA intercalating agent that can only enter bacterial cells with damaged walls.…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%
“…depth (RNA18T150, RNA19T150, DNA18T150 and DNA19T150). The ratios between the 16S rRNA gene and 16S rRNA per cell have been reported to be proportional to the metabolic activity of the cells (Dell'Anno et al, 1998), the rRNA content per cell increasing with metabolic activity. As the MG-1 lineage was detected in RNA18T150 and RNA19T150 libraries, whereas absent in DNA18T150 and DNA19T150 libraries, we suggest that the sediments at 1.5 mbsf could have low cell concentrations of very active MG-1 lineage.…”
Section: Figmentioning
confidence: 99%